TINGKAT PENGETAHUAN DAN SIKAP MAHASISWA DALAM MENGKONSUMSI MAKANAN JAJANAN FOOD PRODUCT DI POLITEKNIK JAKARTA INTERNASIONAL - Tri Yuni Susilowati; Daniaka Sianson Gultom (NHM PRESS, 2022)
Food safety is a very important aspect in everyday life. Lack of attention to this has often resulted in an impact in the form of a decline in the health of consumers. Food selection behavior is influenced by nutritional knowledge, attitudes, and related behaviors. If knowledge, attitudes and actions are still inadequate, then the selection of snacks is not appropriate. This study aims to determine the level of knowledge and attitudes of students in consuming street food products. This observational survey research was carried out at the Jakarta International Polytechnic in November 2021 involving 42 students who met the sample requirements. The results showed that the majority of students' knowledge was in the sufficient category as many as 28 people (67%), while the attitudes of the majority students were in the sufficient category as many as 23 people (55%). The conclusion of this research is that the students' knowledge and attitudes towards street food are quite good.